Republic of Liberia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of the corporate sector accounting, financial reporting, and auditing practices in Liberia. The assessment undertaken is positioned within the broader context of the country s institutional framework and capacity needed to enhance the quality of corporate financial reporting that is a key contributor to improving investor confidence and ultimately economic growth. Efforts are necessary for strengthening the capacity of the regulators and developing accounting and auditing standards in Liberia.